Study on the movement mechanism of rice stem under the action of canopy-opening device based on explicit dynamics simulation - Jing, Lin-long; Wei, Xin-hua; Song, Qi; Wang, Fei (Frontiers in Plant Science, 2023)
The movement mechanism of the rice stem has a significant impact on the spraying effect when rice is sprayed using a sprayer with the canopy-opening device. Rice morphological structure parameters and material parameters were measured to study the movement mechanism of the rice stems under the action of the canopy-opening device, and the canopy-opening process was then simulated using the explicit dynamic method. The simulation scene of the rice canopy-opening process considered the combination of three different heights and three different driving velocities of the canopy-opening device. The movement mechanism of the rice stems under the operation of the canopy-opening device was investigated, and the entire movement process was separated into two stages: contact and oscillation. The simulation results and high-speed photography experimental results show a strong correlation, with a correlation coefficient of 0.733. The simulation results indicate that when the canopyopening device is closer to the ground and the driving velocity is higher, the disturbance to the rice stem during the contact stage is stronger. However, for the oscillation stage, there exists a critical value for both the height and driving velocity of the canopy-opening device. During the oscillation stage, there is a critical value for both the height and driving velocity of the canopy-opening device. The numericalbased explicit dynamics approach was employed in this work to investigate the rice canopy motion mechanism, and this study has a definite reference value for the investigation of complicated motion mechanisms in the field crop production process.